The quantitative relationship between macrobenthic carbon and organic carbon in sediments: A case study of the northern continental shelf of the South China Sea - Tang, Dehao; Liu, Xingjian; Peng, Tianyue; Yang, Xiaohong; Jia, Lei; He, Jian; Huang, Xiaoguang; Xia, Zhen (Frontiers in Marine Science, 2022)
Macrobenthos play an important role in global biogeochemical cycles and carbon energy exchange. Macrobenthic communities on continental shelves are alimented through the sedimentation of organic material. Sedimentary organic carbon is the key step for the carbon cycling within the continental shelf benthic trophic web. However, the quantitative relationship between the macrobenthos and sediments based on total organic carbon (TOC), and the trophic pathways of macrobenthos applied by stable carbon and nitrogen isotope data (δ13C and δ15N) on the continental shelf are still limited. Therefore, the continental shelf of the northern South China Sea (NSCS), with abundant macrobenthos, was chosen as the research area. In this paper, TOC, total nitrogen (TN), δ13C and δ15N of the macrobenthos and sediments, the eco-exergy (Ex), structural eco-exergy (Exst) of macrobenthos communities of the NSCS were analysed. The TOC and TN in macrobenthos varied widely between 1.05% and 71.08% and between 0.29% and 11.36%, respectively, which were much higher than those in sediments. Trophic pathways (food sources and trophic levels) were established by applying δ13C and δ15N values of the main macrobenthic species. The similar stable isotope ratios and the trophic levels of most macrobenthos (2.0–3.4) might indicate similar food compositions and living habits. Eco-exergy grades were positively correlated with the average trophic level value of macrobenthos (correlation coefficient R=0.79). The relationship between the Ex value and the weight of required sediments estimated by the average organic carbon showed a typical positive correlation (R=0.98). This establishment of quantitative relationship provides a useful method for evaluating the structural functions of the ecosystem and researching the carbon sequestration potential of the macrobenthos community.